PEMERIKSAAN SEDERHANA LAPANGAN PPh PASAL 25 TERHADAP KEPATUHAN WAJIB PAJAK - Andi Andi (Jurnal Kajian Akuntansi, 2009)
This study aims to determine differences in corporate tax compliance before and after a simple examination of the field and the influence of Simple Field Inspection of Income Tax Article 25 on taxpayer compliance in meeting tax obligations. This research was conducted at the Tax Office Primary Serang Banten. The research object is the ratio of individual income tax return income tax payable under Section 25 Overpayment of tax payers and after examination by tax inspectors from the year 2003-2007. The research used descriptive research methods and verification. The results (1) the verification shows that there is difference in improving taxpayer compliance corporate income tax overpayment of Article 25 which after a simple inspection, (2) descriptive quantitative Results showed a significant difference between the simple inspection the field of taxpayer compliance. Also see the value of a significance level of 0.05, where t sig of 0.000 <0.05 then the partial correlation coefficients tested were significant. From the calculation of correlation coefficient (R) obtained yield was 0.734 or 73.4%, this indicates that the correlation between the simple inspection the field for income tax overpayment of article 25 of the taxpayer compliance agencies in meeting their tax obligations is strong and has a positive relationship. Keywords: Inspection, Income Tax, Taxpayer Compliance.